THE PRIVATIZATION OF THE PRISON SYSTEM IN THE UNITED STATES: A COMPARATIVE STUDY OF REHABILITATIVE RESOURCES - Witherell, Wendi (2022)
Facing high rates of mass incarceration and prison overcrowding, the United States of America seems to believe that the privatization of its prison system could be a viable solution to the aforementioned problems. Despite the increased incarceration rates of the past few decades, the gradual privatization of the prison system is an understudied area. It is therefore important to understand the rationale behind the movement away from the public sector toward the private sector. This cross-sectional study adopted three theoretical approaches—Models of Incarceration Theory, Political Explanation Theory, and Overcrowding Theory—in an attempt to determine such rationale. It was hypothesized there will be a statistically significant difference in rehabilitative services between government-run prisons and privatized prisons in the United States. Multivariate binary logistic regression results from a sample of 1,009 prisons across the country (N = 1,009) demonstrate that government-run prisons offered more rehabilitative services than those run by the private sector (OR = 2.1, p < .001). The results in this study hold implications for theory, research, social work practice, and policy